Influence of reward system and career development programmes on non-academic employees’ commitment in University of Ibadan, Nigeria (2023)
There is no denying that organisations today are dealing with greater obstacles than before. These issues affect all organisations, regardless of their size, structure, or the type of the goods or services they provide. They are not special to any one organisation or industry. As a result, this study examined the nexus between reward system and career advancement programmes on non-academic employees’ commitment in University of Ibadan, Nigeria. Two specific objectives were raised for attainment. Stratified and simple random sampling techniques were employed to sample three-hundred and sixty (360) respondents. A questionnaire created by the authors tagged ‘Reward System and Career Development Questionnaire “RSCDQ” and Employees’ Commitment Questionnaire ‘ECQ’ was used to obtain information. Analyses of data were done with the aid of descriptive and inferential statistical tools of SPSS. The empirical findings indicated that the reward system has positive and significance influence on employees’ commitment. This showcases that the more favourable the reward system is, the more likely the non-academic employees would demonstrate high degree of commitment in the course of discharging their duties. The empirical outcomes further revealed that career development has a positive and significance influence on level of commitment of non-academic staff. However, it is concluded that both prevailing reward system and career development exercise have great impact on employees’ commitment level. It is recommended that reward system and career development programmes should be enhanced by the concerned stakeholders in order to always guarantee employees’ commitment to duties.